Direct medical cost of metformin and metformin-glimepiride in type 2 diabetes mellitus patients - Sulastri, Sulastri; Hadiq, Shabran; Supadmi, Woro; Perwitasari, Dyah Aryani (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Diabetes mellitus (DM) requires long-term therapy. Selection of the right therapy was very important to provide optimal results at an affordable cost. One of the main standards of oral antidiabetic therapy prescribed for type 2 DM (T2DM) is metformin, either alone or in combination therapy. The purpose of this study was to describe the direct medical costs in type 2 DM patients between metformin and metformin-glimepiride therapy. This research was an observational and descriptive. Demographic and clinical data were taken prospectively from the complete medical records of data patients with the main diagnosis of DM who fulfilled the inclusion criteria in the period January 2019–November 2020 at RSU Nene Mallomo Sidenreng Rappang, South Sulawesi and the two Public Health Centers namely Puskesmas Galur. II and Panjatan II Kulon Progo Yogyakarta. Cost data includes total medical costs from the hospital/ healthcare perspective (cost of drugs, doctor's services and checkups, fees for checking Fasting Blood Glucose/ Gula darah Puasa (GDP) and Blood Glucose Level While/ Gula Darah Sewaktu (GDS)) and total costs from the Badan Penyelenggara Jaminan Sosial (BPJS)/ payer perspective (INA-CBG's rates) were covered by insurance. The results showed that the average direct medical costs at the hospital and the two Public Health Centers respectively were metformin therapy in IDR (Indonesian Rupiah) namely IDR 120.736 and IDR 9.072,- and metformin-glimepiride therapy of IDR 126.298,- and IDR 18.634,-. It can be concluded that the average direct medical cost of metformin therapy is lower than metformin-glimepiride therapy.